Innovative Strategies to Promote Safe Nurse Staffing in the Maternity, Neonatal, and Pediatric Acute Care Setting. Issue 5 (September 2022) - Simpson, Kathleen Rice
Abstract : In this special topics series on nurse staffing, three articles cover innovative strategies critical to promoting safe, high-quality nursing care to mothers, babies, and children. Using the electronic medical record to analyze, predict, and secure nurse staffing based on acuity and census is a concept that all units should be able to operationalize with the help of their electronic medical record vendor. Data from electronic equipment can be engineered for the same purpose. Increasing diversity of the nursing workforce has many benefits to patients, families, and nurses but requires careful sustained planning and commitment. We hope you find these articles valuable in enhancing the discussion and supporting actions to promote safe nurse staffing.